Approximate analytical for degradation of water pollution by effective microorganism (EM) in river - Mohd. Zokri, Syazwani (2014)
In recent years, the interest in preserving the quality of water for distribution processes in order to maximize the fulfillment of various sectors has considerably increased. Be it domestic sources, industrial or agricultural effluents, the massive increase of industrial productions accompanied by high growth of large urban populations has led ti severe water population problems. Various chemical and biological treatments are available for degradation of water pollutions but most of them are not environmental friendly. However, effective microorganism (EM) technology is able to restore and clean water pollutions at low cost. Therefore, mathematical model for water pollutions has been implemented and the effect of EM on degradation of pollutants in river is considered. The model equations which consist of system of three one dimensional non-linear partial differential equations (ODE) has been simulated to describe the degradation of pollutants in river. Homotopy Analysis Method (HAM) is used to solve the system of non-linear PDE. The effect of EM's addition on river pollution is seen from the three cases involving three different initial bacterial concentrations (25mhL-1, 50mgL-1 and 100mgL-1). Based on the results, high bacterial concentrations applied will increase the degradation rate as well as shortening the distance required for pollutant removal.